Improving the Multidisciplinary Treatment of Chronic Pain by Stimulating Body Awareness: A Cluster-randomized Trial. Issue 7 (July 2015) - Van der Maas, Lia C.C.; Köke, Albère; Pont, Menno; Bosscher, Ruud J.; Twisk, Jos W.R.; Janssen, Thomas W.J.; Peters, Madelon L.
Abstract : Background: Because of methodological flaws and a lack of theoretical foundation of body awareness (BA) in previous effect studies of interventions directed to stimulate BA, it is impossible to attribute treatment effects to this specific component of a multidisciplinary treatment. Therefore, this study evaluated short-term and long-term effects of a multidisciplinary pain rehabilitation program with and without psychomotor therapy (PMT), which focused on BA (measured by the scale of body connection) as a primary target of intervention. Methods: Ninety-four patients clustered in 20 treatment groups were cluster randomized, using a biased-coin design, to multidisciplinary treatment as usual with or without PMT. Outcome variables were health-related quality of life, disability, and depression. BA, catastrophizing, and self-efficacy were measured as potential process variables. Assessments were performed at baseline, directly after treatment, and at 3, 6, and 12 month follow-ups. The data were analyzed by linear mixed-model analysis according to the intention-to-treat principle. Results: Data of all 94 patients were used for analyses. After treatment, significant differences favoring PMT were found between conditions on depression (regression coefficient [RC]=−5.01; 95% confidence interval [CI], −8.81 to −1.21), BA (RC=0.23; 95% CI, 0.04 to 0.42) and catastrophizing (RC=−4.76; 95% CI, −8.03 to −1.48). These differences were no longer significant for depression at the 3-month follow-up and for catastrophizing at the 6-month follow-up. Conclusions: No clinical meaningful differences were found between treatment conditions in the primary outcome measures health-related quality of life and disability. However, this is the first long-term RCT that has shown that PMT improves BA in patients with chronic pain and shows good effect size and a significant decrease for catastrophizing.